Interaction Effect of Baseline Serum Glucose and Early Ischemic Water Uptake on the Risk of Secondary Hemorrhage After Ischemic Stroke - Nawabi, Jawed; Elsayed, Sarah; Scholz, Henriette; Kemmling, André; Meyer, Lukas; Kniep, Helge; Bechstein, Matthias; Flottmann, Fabian; Faizy, Tobias D.; Schön, Gerhard; Fiehler, Jens; Hanning, Uta; et al. (Frontiers in Neurology, 2021)
Background and Purpose: Intracerebral hemorrhage (ICH) after mechanical thrombectomy (MT) for acute ischemic stroke (AIS) remains a major complication and its early prediction is of high relevance. Baseline serum glucose (BGL) is a known predictor of ICH, but its interaction with early ischemic changes remains uncertain. We hypothesized that BGL interacts with the effect of tissue water uptake on the occurrence of ICH. Methods: 336 patients with acute ischemic stroke treated with MT were retrospectively analyzed. ICH was diagnosed within 24 hours on non-enhanced CT (NECT) and classified according to the Heidelberg Bleeding Classification. Early tissue water homeostasis has been assessed using quantitative lesion water uptake (NWU) on admission-CT. Multivariate logistic regression was used to identify predictors of ICH. Results: 107 patients fulfilled the inclusion criteria of which 37 (34.6%) were diagnosed with ICH. Patients with ICH had a significant higher BGL on admission (median 177 mgl/dl, IQR: 127-221.75; P<0.001). In patients with low BGL (<120mg/dl), higher NWU was associated with 1.34-fold increased likelihood of ICH, while higher NWU was associated with a 2.08-fold increased likelihood of ICH in patients with a high BGL (>200 mg/dl). In multivariable logistic regression analysis, BGL (OR: 1.02, 95%CI: 1.00-1.04, p=0.01) and NWU (OR: 2.32, 95%CI: 1.44 – 3.73, p<0.001) were significantly and independently associated with ICH, showing a significant interaction (p=0.04). Conclusion: A higher degree of early tissue water uptake and high admission BGL were both independent predictors of ICH. Higher BGL was significantly associated with accelerated effects of NWU on the likelihood of ICH. Although a clear causal relationship remains speculative, stricter BGL control and monitoring may be tested to reduce the risk of ICH in patients undergoing thrombectomy.